The Convergence Behavior of CO2 Emissions in Seven Regions under Multiple Structural Breaks - ACARAVCI, Ali; Erdogan, Sinan (International Journal of Energy Economics and Policy, 2016)
The aim of this paper is to examine the convergence behavior of carbon dioxide emissions per capita (co) in seven regions for 1960-2011 period by using recently developed the second generation panel data methods. Empirical results are as follows: i) there exists cross-sectional dependency for co variable ii) the CADF unit root test without structural breaks shows that the co variable is stationary at its first differences, iii) but the PANKPSS unit root test with structural breaks the co variable is stationary at its level. The overall results indicate that the regional stochastic convergence of carbon emission per capita is valid for the seven regions under structural breaks and any environmental shock has temporary effect. Keywords: Carbon Emissions, Stochastic Convergence, Panel Data. JEL Classifications: C33, Q53, Q56